Review of the flat bug subfamily Calisiinae from Japan, with description of a new genus and four new species (Hemiptera: Heteroptera: Aradidae) - Heiss, Ernst; Shimamoto, Shusuke; Nagashima, Seidai (Zootaxa, 2024)
The Calisiinae (Hemiptera: Heteroptera: Aradidae) of Japan are revised. Four species, all undescribed, are recognized. A new genus, Nipponocalisius gen. nov., is proposed, containing three new species: N. ishikawanus sp. nov., N. tomokunii sp. nov. and N. dimorphus sp. nov. A new species of Aradosyrtis A. Costa, 1864, A. shonoi sp. nov., is also described.